Automatic Fire Extinguishing Installations - Sharapova Madinabonu Baxtiyor qizi; Kushnazarov Pulat Islamovich (European Journal of Life Safety and Stability (2660-9630), 2022)
Automatic fire extinguishing installations are necessary for the rapid impact of detected fires and the elimination of fire. Installations can be compared with a fire brigade, constantly operating in fire stations. Automatic fire extinguishing systems can be installed in almost any room. The most optimal locations for such installations are large closed parking lots, computer control units, production facilities, if necessary, it is possible during the ignition of the production process, archives of documents, etc.